Intervensi Kognitif Spiritual dengan Murottal Ar-Rahman untuk Meningkatkan Penerimaan Diri Pasien Hipertensi - Minanton; Novian Mahayu Adiutama; Wardah Fauziah; Ade Nuraeni; Rosiah; Dwi Diana Putri; Fitri Handayani; Habsyah Saparidah Agustina; Nuridha Fauziyah; Nurizzi Rifqi Ferdian; Bayu Nirwana; Teguh Prawira; Irfani Nurfuadah (Kolaborasi: Jurnal Pengabdian Masyarakat, 2023)
Introduction: Hypertension is a chronic disease which is a main priority in world health problems because it results in death and disability. About 64% of people with hypertension experience physical changes and cognitive impairment. One of the causes of uncontrolled hypertension in sufferers is stress, negative thoughts or depression. Objective: This is motivated by impaired self-acceptance, resulting in sadness, anger, uselessness, hopelessness and weakness, all of which have a negative impact on hypertension. Spiritual cognitive interventions can be used to assist patients in changing negative thoughts into positive thoughts by optimizing spirituality. Therefore, Program Studi Keperawatan Politeknik Negeri Subang collaborates with Puskesmas Cikalapa, Subang to carry out community service with the aim of providing cognitive spiritual interventions with Ar-Rahman murottal to increase self-acceptance of hypertensive patients Method: The method of the activity began with checking the patient's blood pressure and then continuing with giving cognitive-spiritual interventions listening to the murrotal of Ar-Rahman 1-78 through an Mp3 player and earphones, explaining the meaning of Surah Ar-Rahman, and teaching how to be grateful for God's blessings. Intervention was given 3 times in 3 days, 35 minutes a meeting. Result: The intervention was carried out in the target area of ​​ Puskesmas Cikalapa, Subang. The evaluation results of self-acceptance assessment show that 55,38% of hypertensive patients begin to accept their condition, and the remaining 6,15% are depressed, 0% are denial, 24,61% are bargaining and 13,84% are anger. Conclusion: Self-acceptance increases adherence to hypertension management, so puskesmas as a level one service facility needs to apply cognitive spiritual interventions.